Building information modelling (BIM) for structural components in construction. (2nd October 2021) - Hilton, B.D.; Azhar, S.; Khalfan, M.; Ul-Haq, I.
This research explored the use of the structural Building Information Models, as they relate to shop drawings and fabrication. This research attempts to help further identify obstacles that have been preventing the use of BIM on US Army Corps of Engineers (USACE) construction projects. Data was collected by survey from firms that work with the USACE. The survey questions were designed to gather an overall understanding of BIM, its use, the structural aspects of the model, Level of Development, and funding options. It was found that the key obstacles preventing the use of structural BIM modelling, on USACE' projects, were the required level of development to produce shop and fabrication sheets, and the statutory limitations on design dollars. Key recommendations from the results of this research suggest that USACE needs to improve BIM enforcement requirements, and then guide and mentor project team members through the learning curve.